2011
DOI: 10.1037/a0023418
|View full text |Cite
|
Sign up to set email alerts
|

The role of fear and expectancies in capture of covert attention by spiders.

Abstract: Fear-related stimuli are often prioritized during visual selection but it remains unclear whether capture by salient objects is more likely to occur when individuals fear those objects. In this study, participants with high and low fear of spiders searched for a circle while on some trials a completely irrelevant fear-related (spider) or neutral distractor (butterfly/leaf) was presented simultaneously in the display. Our results show that when you fear spiders and you are not sure whether a spider is going to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…This result supports our hypothesis and indicates to what extent uncertainty and uncontrollability may alter the attentional bias in phobic individuals probably by increasing anxiety-related levels. This statement is partly in line with one study in which uncertainty (not sure where a spider is going to be present) enhanced attentional scrutiny for both threatening and neutral/irrelevant stimuli in phobic individuals [28]. That is, uncertainty led to generalized hypervigilance when phobics were not able to predict the appearance of threats.…”
Section: Discussionsupporting
confidence: 86%
“…This result supports our hypothesis and indicates to what extent uncertainty and uncontrollability may alter the attentional bias in phobic individuals probably by increasing anxiety-related levels. This statement is partly in line with one study in which uncertainty (not sure where a spider is going to be present) enhanced attentional scrutiny for both threatening and neutral/irrelevant stimuli in phobic individuals [28]. That is, uncertainty led to generalized hypervigilance when phobics were not able to predict the appearance of threats.…”
Section: Discussionsupporting
confidence: 86%
“…emotional Stroop tasks; Williams, Matthews, & MacLeod, 1996, and in visual search with emotional distractors; Devue, Bepolsky, & Theeuwes, 2011). Our findings therefore require replication using a mixed presentation format, to determine whether similarly effective control is possible when participants cannot predict the nature of an upcoming distractor.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies may seem to suggest that threat stimuli are prioritized for attention (over neutral stimuli) regardless of their relevance to the current task goal (Lipp & Waters, 2007;Mogg & Bradley, 1998). For example, goal-relevant threat targets (snakes) are detected more rapidly than neutral targets (frogs and flowers) in visual search tasks (LoBue & DeLoache, 2008, and goal-irrelevant threat distractors (snakes, spiders) also slow target responses relative to neutral distractors (e.g., butterflies and leaves, Devue, Belopolsky and Theeuwes, 2011;lizards and cockroaches, Lipp & Waters, 2007). Furthermore, studies using the dot-probe task have demonstrated that goal-irrelevant threat distractors that preceded a neutral target (irrelevant cue), speed responses when the threat distractor and target are presented in the same location and slow responses when presented in a different location (Koster, Crombez, & Verschuere, & De Houwer, 2004).…”
mentioning
confidence: 99%